Association between diuretic administration before diagnosis and incidence of acute kidney injury in patients with minimal change disease: A single-center observational study. Issue 18 (7th May 2021) - Shimamura, Yoshinosuke; Abe, Koki; Maeda, Takuto; Ogawa, Yayoi; Takizawa, Hideki; Ishigami, Junichi; Matsushita, Kunihiro
Abstract : Abstract: We examined the association between diuretic administration before the diagnosis of minimal change disease and the incidence of acute kidney injury. Moreover, we examined whether the use of diuretics affected the time to complete remission in adults with such disease. The present study was a single-center, retrospective, observational cohort study. We included 107 patients with biopsy-proven minimal change disease who were treated at a tertiary referral center in Japan between January 1, 2000 and March 31, 2019. All biopsy specimens were examined by a board-certified renal pathologist. The patients were considered to have minimal change disease when the kidney biopsy specimen had no glomerular lesions or only mild focal mesangial prominence (not exceeding 3 or 4 cells per segment) by light microscopy and/or foot process effacement by electron microscopy. Logistic regression and Kaplan–Meier curve analyses were performed, comparing the data of patients who received diuretics or not. The median age was 47 (28–66) years, 52% of patients were women, and the median proteinuria dosage was 8.3 (5.3–11.2) g/d. When minimal change disease was diagnosed, 27% of patients were taking diuretics. Within 30 days after the diagnosis, acute kidney injury occurred in 27% of patients. On multivariable logistic regression analysis, the use of diuretics was significantly associated with a higher risk of acute kidney injury. The use of diuretics was also associated with a longer time to complete remission. Diuretic administration can be associated with an elevated acute kidney injury risk and longer remission time in adult patients with newly diagnosed minimal change disease.